Reposisi Kaum Bapak Katolik Keuskupan Manado Demi Penguatan Pelayanan Komisi Keluarga dalam Spiritualitas Pro Familia, Ecclesia et Patria - Herkulaus Mety (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2026)
This study analyzes the existence of the Catholic Fathers' Group within the Manado Diocese, and its profound implications for family ministry, economic empowerment, and divorce prevention. Operating under the auspices of the Diocesan Family Commission, the KBK must uphold a non-elitist, egalitarian ethos, truly serving its members with a spirituality dedicated to the family, the Church and the nation. The research employs a multidisciplinary approach, integrating philosophical, ethical, psychological, modern organizational management, and pastoral perspectives. Philosophically, it explores the essence of Catholic fatherhood; ethically, it scrutinizes accountability and moral leadership; psychologically, it addresses inter-relational dynamics and resilience; managerially, it proposes modern and organizational governance models for effective, scalable operations; and pastorally, it assesses its role in the Church’s communio mission. The central finding is that the KBK’s successful repositioning is crucial for strengthening the Family Commission’s ability to execute its core mandates. The study proposes a contemporary, professional governance model utilizing modern human resource and organizational management principles to ensure sustainable impact and real-world service delivery, particularly in family economic resilience. This transformation ensures the KBK is a true servant-leader body, upholding the principle of servant leadership and manifesting Christ’s love in every Catholic family.